The Impact of Educational Intervention Based on Health Belief Model on Promoting Self-Care Behaviors in Patients with Smear-Positive Pulmonary TB - Khir Mohamad jadgal; Iraj zareban; Hadi Alizadeh-Siuki; Hossein Izadirad (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: One of the most common infectious diseases is Tuberculosis. It yearly causes more than 2 million death in the world. This study aimed to determine the impact of health education based on Health Belief Model on promoting self-care behaviors in patients with smear-positive pulmonary tuberculosis in Chabahar in 2013. Methods: Framework of this quasi-experimental study was Health Belief Model. Data was collected by researcher-made questionnaire. 80 TB patients were selected as samples through classified random sampling and divided into case and control groups. Educational sessions for case group were performed through face-to-face and question-and-answer sessions in 2 training sessions for 2 month. No educational intervention were done on control group. Training materials were manuals and pamphlets. Both groups were followed for one month after the intervention to perform a post test. The data collected were analyzed by using SPSS16 software and descriptive and analytical tests. Results: The mean scores of perceived severity, perceived benefits, perceived barriers, cause to action, self-efficacy, knowledge and self-care behaviors were increased significantly following intervention and paired sample t-test showed a significant change in the case group, but this change was not significant in the control group. Conclusion: Health education promotes self-care behaviors of TB patient through Health Belief Model. Paper Type: Research Article.